Swimming Upstream in Turbulent Waters: Auditing Agile Development - Gupta, Manish; Krishnamachariar, Priyadarsini (Information Technology Risk Management and Compliance in Modern Organizations, 2018)
This title is an IGI Global Core Reference for 2019 as it is one of the best-selling reference books within the Computer Science and IT subject area since 2017, providing the latest research on information management and information technology governance. This publication provides real-world solutions on identifying, assessing, and managing risks to IT systems, infrastructure, and processes making it an ideal publication for IT professionals, scholars, researchers, and academicians. Information Technology Risk Management and Compliance in Modern Organizations is a pivotal reference source featuring the latest scholarly research on the need for an effective chain of information management and clear principles of information technology governance. Including extensive coverage on a broad range of topics such as compliance programs, data leak prevention, and security architecture, this book is ideally designed for IT professionals, scholars, researchers, and academicians seeking current research on risk management and compliance.